Multihoming in Multihomed AD HOC Networks with SCTP - Dutt, Sarthika; Sharma, Astha; Saxena, Anuj (International Journal of Computer Sciences and Engineering, 2025)
SCTP multi-homing is the independence to choose its transmission route from the given alternative routes by a node, ad-hoc networks are independent of the infrastructure and are created on demand driven processes giving multihoming functionalities to the system, Controlled at the network layer of the system. IETF rules at transport layer have mentioned all the multihoming characteristics of the system. This research prioritize multihoming feature at both network and transport level and aims to prove the SCTP functionalities over DSR ad-hoc system. Afterwards the dysfunction of the multi- homing feature, introduces CLI(cross layer interface) for added multihoming functionality. The simulation in NS2 is utilized for design and simulates the study. In case of network failure, the multihoming has enhanced the good put rates. Multihoming is better for simultaneous fast retransmission policies, the results provided gives an idea of multihoming advantages